INTERVENTIONS OF THE TOURIST URBANIZATION PROCESS IN PRAIA DE IRACEMA, FORTALEZA (CE) - Barbosa, Jéssica Mesquita; Paula, Davis Pereira de (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.957, 2020)
The study deals with the spatial transformations that took place at Praia de Iracema, an important tourist and leisure spot in the capital of Ceará. Tourist practices on the northeastern and Ceará coast are discussed, as well as related public and private initiatives. Therefore, based on a progressive-regressive methodology by Lefebvre (1979), the influences of urbanization and globalization on the Fortaleza coast are investigated through economic investments in tourism products on a regional and national scale. Certainly, from programs such as Prodeturis, and Prodetur / NE I and II, the beach has become a territory of local and international interest, mainly after its reappropriation and revitalization between the 1970s and 2020. It is assumed that these actions were motivated by the practice of tourism as a modern recreation and leisure activity, increasingly antropophizing the landscape.